Pola bakteri dan kepekaannya terhadap antibiotik yang ditemukan pada ruang kelas dan ruang small group discussion (sgd), Program Studi Pendidikan Dokter, Fakultas Kedokteran, Universitas Udayana - Luh Putu Dea Sasmita Pralambari; Komang Januartha Putra Pinatih (Universitas Udayana, 2018)
Class room and Small Group Discussion (SGD) room are the places that are often visited by the students of Faculty of Medicine, Udayana University. Beside as a place for daily teaching-learning activity, those rooms can be as well used for any kinds of students activity such as organizational activity, non-formal activity, and many other student activities. As there are many students that come in and use the rooms everyday, the rooms may have risk for bacterias growth and development. The bacteries can be both good bacteries and bad bacterias (pathogen). It is necessary to conduct a research to know the pattern of the bacterias in the rooms. The samples of this research were taken from both class room and SGD room, Faculty of Medicine, Udayana University. The collected samples were then processed in the Microbiology Laboratorium, Faculty of Medicine, Udayana University to achieve data that can be analyzed and then reported. Based on 28 studied samples, the result showed that Staphylococcus aureus had the highest percentage of 50%, then Acinetobacter baumannii became the second with percentage 25%, then Shigella spp. 15%, and the last were both Stenotrophomonas maltophilia and Burkholderia cepacia with percentage of each was 5%. Sensitivity test results showed that Acinetobacter baumannii was sensitive to meropenem, doxycicline, gentamycin, and tetracyclin, but resistant to ceftriaxone. Keywords: Patterns of bacteria, sensitivity, antibiotics, Acinetobacter baumannii